Power Electronics for Renewable Energy Sources - Islam, S.; Chem, N.; Abu-Siada, Ahmed; Mubashwar, H. (Elsevier, 2017)
With this book in hand, engineers will be able to execute design, analysis and evaluation of assigned projects using sound engineering principles and adhering to the business policies and product/program requirements.